HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS V SD NEGERI 02 PURWOREJO - Yona Intan Zariska; Ratna Setyaningsih (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study aims to examine the relationship between learning motivation and mathematics learning achievement of fifth-grade elementary school students. Learning motivation is a critical factor influencing student success, particularly in subjects that require concentration and continuous practice, such as mathematics. This research employed a quantitative correlational design with a sample of 9 fifth-grade students. Data were collected using a learning motivation questionnaire and mathematics learning scores, then analyzed using descriptive statistics and Spearman Rho correlation test with SPSS. The results indicated that students’ learning motivation was in the high category with a mean of 44.56 and standard deviation of 4.13, while mathematics learning achievement ranged from good to very good with a mean of 86.56 and standard deviation of 5.34. Spearman Rho correlation analysis revealed a very strong and significant relationship between learning motivation and mathematics learning achievement (r = 0.949, p < 0.01). This finding confirms that increasing students’ learning motivation positively affects their mathematics achievement. The study suggests that teachers should continuously motivate students to improve mathematics performance.